The thin line between legitimate and criminal enterprises: subsidy frauds in the European Community - Passas, Nikos (Crime, law and social change, 1993)
This paper describes and analyses a large fraud against the financial interests of the European Community (EC). On the basis of this case and our interviews with officials in five EC countries, we highlight structural impediments to the control of such frauds, draw parallels with other research on organisational crime and suggest that the distinction between "organised crime" and "white-collar crime" be abandoned in favour of an "enterprise model" of crime. We conclude by pointing out that legal changes and strict controls alone cannot substantially reduce the huge potential for EC frauds, especially in view of the abolition of EC's internal borders in 1993. Antifraud policies must also address the underlying structural factors.